KONSTRUKSI KURIKULUM STEM BERBASIS ETNOSAINS: TRANSFORMASI PENGETAHUAN LOKAL BUDIDAYA BAWANG MERAH BREBES MENJADI MATERI KONSEP DASAR IPA SD - Dwiba Elisa; Fintia Destriana; Adisya Nur Fadillah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to reconstruct the indigenous knowledge of shallot cultivation in Brebes Regency into formal science concepts within the STEM (Science, Technology, Engineering, and Mathematics) framework for the Basic Concepts of Elementary Science course in PGSD. This research applies an exploratory qualitative approach combined with the Model of Educational Reconstruction (MER). Data were collected through participatory observation, in-depth interviews with expert farmers, and document analysis. The results showed that traditional practices such as agricultural canal irrigation (siraman), night light traps (grogol), and soil mounding (larikan) contain valid scientific principles. "Siraman" relates to soil capillarity, "grogol" reflects positive insect phototaxis and optical refraction, while "larikan" manipulates soil aeration and gravity. These local components were successfully synthesized into a structured STEM-Ethnoscience matrix framework. This curriculum construction bridges textual academic science and community empiricism, equipping prospective elementary school teachers with place-based pedagogical skills.